Uspešnost preizkusa risanja ure pri nedementnih slovenskih starostnikih z različno izobrazbo - Avberšek, Andreja (Zdravniški vestnik, 2005)
Background. Early detection of dementia has a number of benefits such as pharmaceutical intervention, improved recognition and treatment of comorbid medical disorders. Brief cognitive tests have an important role in initial screening for dementia. So far, only the Mini Mental State Examinatiou (MMSE) has been introduced in Slovenia. The MMSE can be complemented with the Clock-Drawing T'est (CDT). A standard procedure ofapplying and evaluating CDT as well as normative values for Slovenian population are yet to be defined. Our aim was to apply CDT to normal subjects of different age and educational level. Our hypothesis was that education level has no significant effect on performance on CDT. Methods. 132 normal subjects aged 55 to 79 years were enrolled in the study. None of them met the DSM IV criteria for dementia. Clock drawings were evaluated using the Shulman scale. Analysis of variance (ANOVA) was performed to compare different age groups. Results. Statistical analysis showed no significant effect of gender (p = 0.88, F = 0.023) and education (p = 0.55, F = 0.77) on clock drawing. CDT performance significantlydeteriorated with age (p = 0. 000024, F = 7.34). Conclusions. Since we found no significant effect of education on CDT; the hypothesis was accepted. Deterioration of CDT results with age can only partly be attributed to the process of aging. It is highly probable that in a certain number of participants the process of dementia had already started, yet the clinical criteria were not met at the time. Our group of subjects is going to be used as a control group in the process of validation of CDT.
Keywords: Aged; Analiza variance; Analysis Of Variance; Cognition Disorders; Demenca; Dementia; Diagnosis; Educational Status; Izobrazbeno stanje; Memory Disorders; preizkus risanja; Spomin, motnje; Spoznavne motnje; Starostniki